Peran Organisasi Wartawan dalam Meningkatkan Profesionalisme Wartawan (Studi Kasus Persatuan Wartawan Indonesia Aceh Jaya) - Nurul Bayani; Anhar Fazri (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
The current condition of journalists is still not enough to be said to be professional, this is proven by the large number of violations of the code of ethics in the media in delivering news or information. Journalist organizations must have synergy, integrity, and credibility that aim to build the spirit of professionalism of journalists, so that they can develop professional press freedom in the future. This study uses a descriptive method with a qualitative approach. The results showed that the Indonesian Journalists Association (PWI) Aceh Jaya as an organization has played a role in increasing the professionalism of journalists. This can be seen from the many positive impressions from the people of Aceh Jaya regarding the performance of Aceh Jaya journalists. The professionalism of Aceh Jaya journalists is also seen by their understanding of the journalistic code of ethics and responsibilities as a journalist. In delivering news, it is always timely and actual and there are many activities and programs carried out by PWI Aceh Jaya, including training and competency testing for PWI Aceh Jaya members who have just joined as well as conducting socialization related to journalism.